Penerapan Metode SAW dalam Penentuan Mata Pelajaran Pilihan Siswa Kelas XI pada MAN 1 Brebes - Saputro, Risky Wisnu; edi, sarwo; Perdana, Willy Yudha; Nugroho, Kristiawan; Ardhianto, Eka (Jurnal Informatika: Jurnal Pengembangan IT, 2025)
The subject selection process for eleventh-grade students at Madrasah Aliyah Negeri 1 Brebes faces challenges including misalignment between student interests and academic abilities, and imbalanced teacher-to-subject ratios across Natural Sciences, Social Sciences, and Religious Studies. This study develops a decision support system using the Simple Additive Weighting (SAW) method to provide objective recommendations that consider both academic performance and student preferences. A quantitative descriptive analytical approach was applied with data from 30 tenth-grade students, incorporating four criteria: Natural Sciences scores, Social Sciences scores, Religious Studies scores, and student interests, weighted 0.25, 0.25, 0.10, and 0.40 respectively. The SAW implementation included decision matrix construction, normalization, weighted preference calculation, and recommendation determination. Results showed optimal distribution with 19 students recommended for Natural Sciences, 7 for Social Sciences, and 4 for Religious Studies, achieving 96.67% accuracy in aligning preferences while optimizing academic potential. The system preserved preferences for all students initially interested in Social Sciences and Religious Studies, while reassigning two Natural Sciences–interested students to Social Sciences based on superior performance. Top-performing students identified were Mohammad Abian for Natural Sciences (0.9802), Julia for Social Sciences (0.87243), and a student with 0.75995 for Religious Studies. The SAW method proves effective in addressing multi-criteria decision-making while ensuring transparency, objectivity, and balanced resource use in Islamic secondary education.